Digital CCTV : a security professional's guide - Harwood, Emily (Elsevier/Butterworth-Heinemann, 2008)
The effects of digital technology on the security industry require constant vigilance by security distributors, sales staff, and installation professionals. Today and for the foreseeable future, all security professionals must have at least a basic understanding of digital technology. Digital CCTV addresses this new challenge. Topics convered include compression variables such as Lossless and Lossy, which are explained by reviewing Huffman and Run Length Encoding (RLE), and by relating these forms of compression to ZIP and Stuffit, which are commonly used in personal computers.